(untitled) (Medical Forum Monthly, 2024)
Objective: This purpose of this study is to evaluate the outcomes of Ponseti manipulation and casting technique in treating Idiopathic Congenital Clubfoot in children under three years of age. Study Design: Descriptive study Place and Duration of Study: This study was conducted at the Department of Orthopaedic Surgery, SKBZ Medical Complex Quetta from 1st September 2021 to 31st August 2022. Methods: The study included 93 feet of 55 patients with idiopathic club foot deformity, of both genders, age from 1 week to 3 years. The deformities were corrected using the Ponseti manipulation and casting technique. Pirani Scoring System was utilized, while SPSS version 16.0 used to analyse the data. Results: In this study, we included 55 clubfoot patients, 93 feet, with 37 males and 18 females. 9 cases had right-sided involvement, and 38 were bilateral. The pre-correction Pirani score ranged from 4 to 6, with a mean of 5.7, while post-correction scores ranged from 0 to 1, with a mean of 0.5. The mean age of the patients was 2.2 years, ranging from one week to three years. The Ponseti method resulted in 92.7% excellent outcomes. Conclusion: We concluded that Ponseti technique was non-invasive, safe and provides efficient, satisfactory outcomes for the management of idiopathic congenital clubfoot in children presenting up to the age of three years. Key Words: Idiopathic Congenital talipes equinovarus, Pirani scoring, Ponseti technique.